A practical approach to constructing hierarchical networks for urban hazard mitigation planning using GIS: The case of Futian, Shenzhen. (June 2018) - Jiang, Xue; Song, Jusheng; Lin, Yaoyu; Gong, Yongxi
Abstract: Urban disasters can cause extensive losses of life and property, but these losses can be reduced by systemic and spatial planning for urban hazard mitigation (UHM). The emergency facilities are composed of emergency shelters (ESs), evacuation routs (ERs), and emergency shelter zones (ESZs) and these components play an important role in UHM. Constructing a hierarchical network is an effective approach to layout the emergency facilities. This paper proposes a conceptual framework to construct a hierarchical UHM network based on Central Place Theory and suggests a practical approach using geographic information systems (GIS). In the proposed method, the configuration of ESs considers the population distribution, security, fairness, and accessibility using GIS to meet the survival needs of refugees, provide required materials and coordinate rescue and relief efforts. The minimal cost path linking an ES to the higher level ES is calculated to be the ER for material transport and transferring refugees via GIS network analysis function. The ESZs of the ESs at each level can be partitioned using a bottom-up algorithm based on the relationships among hierarchical ERs, which can support policy and strategy development for emergency administrative management. This paper provides a practical approach to constructing a hierarchical UHM network for earthquakes that can reduce disaster losses and enhance the efficiency of rescue and relief efforts to decrease urban vulnerability. Highlights: Constructing hierarchical network is an effective method to layout emergency facilities in spatial urban hazard mitigation using GIS. The configuration of emergency shelters (ESs) should consider the population distribution, security, fairness, and accessibility. Evacuation routs (ERs) are the minimal cost paths to connect hierarchical ESs. A bottom-up algorithm is used to partition hierarchical emergency shelter zones (ESZs) based on the relationships of ESs and ERs.